A 1p31.3 deletion encompassing the nuclear factor 1A gene presenting as possible temporal lobe epilepsy in association with schizoaffective disorder. Issue 4 (4th July 2022) - Colijn, Mark A.; Hrynchak, Monica; Hrazdil, Chantelle T.; Willaeys, Veerle; White, Randall F.; Stowe, Robert M.
ABSTRACT: Chromosome 1p32-p31 deletion syndrome, which is characterized by a variety of neurodevelopmental abnormalities, is thought to occur as a result of nuclear factor 1A ( NFIA ) haploinsufficiency. We present a case of a right-handed 40-year-old female with a 1p31.3 deletion, who exhibited numerous common features of this syndrome, in addition to treatment resistant schizoaffective disorder and possible temporal lobe epilepsy, making her presentation unique. While neither psychosis nor temporal lobe epilepsy has been described in this syndrome previously, these conditions likely occurred in our patient as a result of NFIA haploinsufficiency.